Gambling With Lives : A History of Occupational Health in Greater Las Vegas - Turk, Michelle Follette, 1981- (Book collections on Project MUSE., 2021)
"Gambling with Lives is a history of occupational health and the conflicts between workplace safety and regulations in Las Vegas, Nevada. The revised and expanded edition is updated through 2020 with new discussions of the Harvest Festival Shooting, Legionnaire's disease outbreaks at the resorts, work-related disorders in the service industry, and COVID-19"--